If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x(7 + -1y) + 7 = -4 (7 * -2x + -1y * -2x) + 7 = -4 (-14x + 2xy) + 7 = -4 Reorder the terms: 7 + -14x + 2xy = -4 Solving 7 + -14x + 2xy = -4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -14x + -7 + 2xy = -4 + -7 Reorder the terms: 7 + -7 + -14x + 2xy = -4 + -7 Combine like terms: 7 + -7 = 0 0 + -14x + 2xy = -4 + -7 -14x + 2xy = -4 + -7 Combine like terms: -4 + -7 = -11 -14x + 2xy = -11 Reorder the terms: 11 + -14x + 2xy = -11 + 11 Combine like terms: -11 + 11 = 0 11 + -14x + 2xy = 0 The solution to this equation could not be determined.
| -4(x+1)=-13-4x | | 5/6(18)+3/7(28) | | 36t=78 | | 12=8-4(n+1) | | 3(d+8)=3d | | x/3+25=33 | | 6r+4=18 | | 11-5(9x+2+4x-8)=-4(10x+42)-23 | | 5(9/25) | | 23/4k+3/4+6=64/5 | | n/7=5.55 | | 6+2a*3b-4a+5= | | 8+2(a-5)= | | -5y-10=-1-3(4y-11) | | 6-7x=10x+10 | | -3-3x=-3(x+1) | | 4(4m-5)+4=6(2m-6) | | 13=x/3+4 | | .75x+6=.66x-8 | | 3r-9=0 | | 2x+7=-53 | | 40-8x/x-5 | | 6/7(x+1)=1/21(x+2) | | 3(x-5)+5x=8(x+1) | | -9=-2--3r | | 7(-5x-2)= | | 3(y-10)+1=.25(y-8) | | -1(7-y)+4=-4 | | u+4=11-2(2u-9) | | 2(3b+2)-7=9 | | 13-4/2x=37 | | x^2+13x+65=0 |